2023
DOI: 10.1186/s13019-023-02162-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hybrid procedure on pulmonary arterial dimensions and right ventricular load after biventricular repair

Abstract: Background Hybrid procedure with ductal stenting and bilateral pulmonary banding offers a temporary approach in high-risk neonates with complex congenital heart defects aiming biventricular repair. This procedure may also have negative impact concerning post-banding pulmonary stenosis resulting in right ventricular pressure load. Methods Between 2010 and 2021 we identified 5 patients with interrupted aortic arch and complex congenital heart defect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In our setting, we put patients with bilateral PAB and ductal stent on a home-monitoring programme. Our intention is to keep the bilateral PAB not too long (median age at BVR was 78 days) as others also have observed that a longer period with bilateral PA-bands (>90 days) increases the risk of reinterventions [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our setting, we put patients with bilateral PAB and ductal stent on a home-monitoring programme. Our intention is to keep the bilateral PAB not too long (median age at BVR was 78 days) as others also have observed that a longer period with bilateral PA-bands (>90 days) increases the risk of reinterventions [ 15 ].…”
Section: Discussionmentioning
confidence: 99%